2018
DOI: 10.1158/1078-0432.ccr-17-3800
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diagnosis of Diffuse Gliomas through Sequencing of Cell-Free Circulating Tumor DNA from Cerebrospinal Fluid

Abstract: Purpose: Diffuse gliomas are the most common primary tumor of the brain and include different subtypes with diverse prognosis. The genomic characterization of diffuse gliomas facilitates their molecular diagnosis. The anatomical localization of diffuse gliomas complicates access to tumor specimens for diagnosis, in some cases incurring high-risk surgical procedures and stereotactic biopsies. Recently, cell-free circulating tumor DNA (ctDNA) has been identified in the cerebrospinal fluid (CSF) of patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
133
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(145 citation statements)
references
References 20 publications
4
133
0
Order By: Relevance
“…Physiologic factors include those that limit the amount of tumorderived cfDNA present in the CSF. Multiple studies have shown that low grade tumors or those not directly communicating with the CSF space have low to undetectable tumor-derived cfDNA in the CSF Juratli et al, 2018;Martínez-Ricarte et al, 2018;Pan et al, 2019). Likewise, detection of tumor-derived cfDNA is less likely in patients with new onset disease (Pan et al, 2019).…”
Section: Preanalytical Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Physiologic factors include those that limit the amount of tumorderived cfDNA present in the CSF. Multiple studies have shown that low grade tumors or those not directly communicating with the CSF space have low to undetectable tumor-derived cfDNA in the CSF Juratli et al, 2018;Martínez-Ricarte et al, 2018;Pan et al, 2019). Likewise, detection of tumor-derived cfDNA is less likely in patients with new onset disease (Pan et al, 2019).…”
Section: Preanalytical Variablesmentioning
confidence: 99%
“…A panel of seven genes (IDH1, IDH2, TP53, TERT, ATRX, H3F3A, and HIST1H3B) has been developed that can accurately classify nearly 80% of malignant gliomas based on genetics alone. A retrospective study of 20 glioma patients demonstrated that this combined digital PCR and targeted sequencing panel could use CSF cfDNA to correctly classify gliomas in 85% of cases and only failed with low grade tumors or those not in direct contact with the ventricles(Martínez-Ricarte et al, 2018).…”
mentioning
confidence: 99%
“…Regarding the diagnostic potential of CSF cfDNA analysis, evaluation of a selected panel of molecular alterations in CSF cfDNA allowed the identification of tumour molecular alterations in 17/20 (85%) cases of diffuse gliomas, allowing their classification according to the latest WHO criteria . Also, detection of mutations affecting histone H3 genes in a case series of paediatric brain tumours showed high sensitivity and specificity: 87.5% and 100% respectively .…”
Section: Circulating Cell‐free Nucleic Acids Analysismentioning
confidence: 99%
“…In CNS tumors, detection of ctDNA in the peripheral blood is possible, but sensitivity appears to be a challenge in these patients . Instead, recent efforts have focused on detection of tumor DNA in the CSF . Given the paucity of data from studies of ctDNA in children with hematologic and CNS malignancies, our review will focus on current technologies being applied to interrogate ctDNA in children with non‐CNS solid tumors.…”
Section: Introductionmentioning
confidence: 99%